Prevalence and Correlates of Vitamin B12 Deficiency among Depressive Patients Presenting in the Tertiary Care Hospital of Gandaki Province of Nepal - Khattri, Jai Bahadur; Godar, Srijana Thapa; Subedi, Anil (Birat Journal of Health Sciences, 2020)
Introduction: The prevalence of vitamin B12 deficiency in depression is not clear and more research is needed. Objectives: The objective of this study is to find the prevalence of deficiency of vitamin B12 level in the depressed patient. The second objective is to find the prevalence of deficiency of vitamin B12 according to different socio-demographic variables. Methodology: The patients diagnosed as depressive episodes according to the International Classification of Disease – 10 Classification of Mental and Behavioural Disorders were selected from the Psychiatric Out-Patient Department of Manipal Teaching Hospital, Pokhara. The proforma was used to collect the socio-demographic profile of the patient. The serum sample of the 50 patients was sent for vitamin B12 estimation. Serum concentrations less than 239 pg/ml was considered deficient in this study. Results: The overall prevalence of vitamin B12 deficiency was 22% in the depressed patients. The mean age of the total patients were 39.2 years with the standard deviation of 13.75 years. Vitamin B12 deficiency was more prevalent in the socio-demographic variables like age above 61 years, Brahmin and Chhetri caste, female gender, unmarried groups, and in the patients living in the urban area as compared to other variables. Conclusion: The result shows that vitamin B12 deficiency is common in the patients with depression. Clinicians should be aware of the risk for vitamin B12 deficiency in depressive patients. As this study was done in limited geographical area and sample size being small, further larger studies are needed before generalizing these results.